Intrahepatic Cholestasis of Pregnancy and Transaminitis in Women with COVID-19: A Case Series - Waldrop, Anne R.; Henkel, Andrea; Lee, Kelley B.; Druzin, Maurice L.; Aziz, Natali; El-Sayed, Yasser; Lyell, Deirdre J. (American Journal of Perinatology Reports, 2024)
Objective The four initial severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-infected pregnant women presenting at term gestation to our institution presented with transaminitis. Three of the four were diagnosed with intrahepatic cholestasis of pregnancy (IHCP). Growing evidence exists of an associated transaminitis in nonpregnant SARS-CoV-2 patients. However, there are limited data of hepatic involvement of SARS-CoV-2 in pregnancy, and no previous studies have assessed the association with IHCP in patients with coronavirus disease 2019 (COVID-19).Study Design This was a retrospective, single-center case series of four consecutive pregnant women with a positive result for SARS-CoV-2 presenting with transaminitis in third trimester.Results The clinical courses of four pregnant women with COVID-19 and transaminitis, three of four of whom were diagnosed with IHCP, are described. Testing for SARS-CoV-2 was done through a reverse transcription polymerase chain reaction test of a nasopharyngeal swab.Conclusion As we await larger studies ascertaining the incidence of IHCP in SARS-CoV-2, this prevalence highlights the importance of diagnosing IHCP among women with COVID-19 as a potential etiology of transaminitis, as IHCP risks may be ameliorated with earlier delivery. Moreover, delineating a hepatobiliary association in pregnancy may provide further information about the mechanism of liver impairment in SARS-CoV-2 in all patients.
Keywords: COVID-19; IHCP; intrahepatic cholestasis of pregnancy; maternal; novel coronavirus; SARS-CoV-2; transaminitis